PROFIL PEMBELAJARAN UNGGAH-UNGGUH BAHASA JAWA DI SEKOLAH DASAR - Muh. Arafik; Rumidjan Rumidjan (Universitas Negeri Malang, 2016)
Abstract: the aimed of this research is to described the model of teaching politeness in Javanese language at elementary school. the variety of activities that is done by the teacher’s and the students during the process of teaching politeness in javanese language subject at SDN Penanggungan Malang. The approach that was used in this research is qualitative methodology. The data was collected during the process of teaching javanese langage subject at SDN Penanggungan Malang which is done through the problem case study used qualitative analysis. Therfore, this research will result in the construction models of the practice teaching politeness in javanese language at elementary school. Model immersion learning is model of teaching which has attempt to directly involve the students in the learning process. Abstrak: Tujuan penelitian ini untuk mendeskripsikan model Pembelajaran Unggah-Ungguh Bahasa Jawa di Sekolah Dasar. Aktifitas apasaja yang dilakukan oleh siswa dan guru dalam pembelajaran unggah-ungguh Bahasa Jawa di SDN Penanggungan Kota Malang. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Data diperoleh melalui praktik Pembelajaran Bahasa Jawa di SDN Penanggungan Kota Malang, melalui penelitian studi kasus dengan analisis kualitatif, maka penelitian ini akan menghasilkan konstruksi Model Praktik Pembelajaran Unggah-Ungguh Bahasa Jawa di Sekolah Dasar. Model Immersion Learning adalah model pembelajaran yang berupaya mencelupkan langsung diri siswa ke dalam proses belajar.